Transformasi Pendidikan Jasmani Di Era Modern: Studi Literatur Tentang Inovasi, Gaya Hidup Sedentari, Dan Pengembangan Guru - Zulfan Heri; Putra Arima; Christhover Latersia Limbeng; Fitri Rosanni Hutapea; Raju Rafdo Saragih (Jurnal Keluarga Sehat Sejahtera, 2026)
The transformation of physical education in the modern era has undergone significant developments in line with technological advances, changes in societal lifestyles, and increasingly complex teacher competency demands. This article aims to examine innovation trends in physical education, the impact of a sedentary lifestyle on students' physical activity, and the importance of professional development for physical education teachers. The method used is a literature study by analyzing various journals, books, and relevant scientific sources published in recent years. The results of the study indicate that the use of digital technology, innovative learning models, and physical activity-based approaches can increase student motivation and participation in physical education learning. On the other hand, the increasing sedentary lifestyle poses a serious challenge because it impacts student health and fitness. Therefore, physical education teachers are required to continuously develop pedagogical, professional, and digital competencies to adapt learning to the needs of the modern era. In conclusion, the transformation of physical education is a crucial step in creating a healthy, active, and adaptive generation.